The role of Majallah Ahkam Al-Adliyyah in developing conceptual sukuk model based on maqasid shariah: A qualitative study - Muhammad Azizur Rahman, Ramli; Mansor, Sulaiman; Noor Faezah, Basary (Asian Scholars Network, 2019)
The objective of the Islamic capital market is to mobilize and transfer the funds from one sector to one sector of the economy for benefit of human life. Its main objectives are to eliminate the riba and develops the Islamic global economy. (Securities Commission, 2009). These two objectives are the same meaning in the Maqasid Shariah framework. Sukuk is an Islamic investment certificate that funds large scale projects which is Sukuk Ijarah, Sukuk Mudarabah and Musyarakah is the most issued in Islamic countries. Maqasid shariah can be implemented through the framework of fiqh awlawiyat (priority) either in the stage (dhoururi) or stage of need (hajiyat) or stage of perfection (tahsiniyat). Asyraf Wajdi (2008). The general purpose of the study is to develop a new sukuk model based on Maqasid Shariah via the code of Majallah ahkam al-adliyyah. The research found the 4 main themes appear. Firstly, the understanding of the contracting parties is important to avoid misuse and raising distress (raf'ul haraj) via the maddah 2-3. Secondly, implementation of the method Dar’ul Mafasid inside sukuk model to preserve the maslahah daruriyat via the maddah 30. Thirdly, implementation of method Al- Ghurumu Bil Ghunmi and Al-Kharaj Bi Daman In the Sukuk Musyarakah to preserve the maslahah Hajiyat via the maddah 85 – 87. Lastly, implementation of elimination of the harmful matter inside the sukuk model that can keep the justice between the sukuk issuer and the investor via the maddah 25-27. As a conclusion, the legal maxim inside the majallah ahkam al-adliyyah could explain further more how to achieve maslahah and keep away from mafsadah in the future sukuk model.